THE EFFECTIVENESS OF THE “LAYANAN KESEHATAN CUMA-CUMA DOMPET DHUAFA NUSA TENGGARA TIMUR” FROM “KAWASAN SEHAT” PROGRAM : EFFORTS TO REDUCE STUNTING PREVALENCE IN OEBELO VILLAGE - Selawati, Selawati; Shafira Salsabila Samara; Martina Tirta Sari; Kurnia Amelia; Danan Panggih Wisastra; Fitri Ayu Rahmawati; Ummi Kalsum Muhammad (Media Gizi Indonesia, 2025)
Stunting is a failure of child growth characterized by a lack of height for age Z-score caused by chronic nutritional problems. Stunting has a negative impact on the quality of human resources in the future. Nusa Tenggara Timur (NTT) is the province with the highest stunting cases in Indonesia. LKC Dompet Dhuafa NTT  help to accelerate stunting mitigation carried out in Kawasan Sehat Program. The study aimed to determine the effectiveness of stunting interventions through The Kawasan Sehat Program in Oebelo Village. This research is a qualitative and quantitative evaluative research with input-process-output approach. The selection of informants purposive sampling technique with seven informants. Primary data were collected by interviews and observations. Meanwhile, secondary data is carried out by reviewing documents. In the input component, there are still constraints in the adequacy of facilities, infrastructure, and cadre transportation. In the process component, necessary to enhance partnerships and strengthen the commitment of the target groups of the program. In the output component, there has been a decrease in stunting prevalence from 8% to 4%. There are several factors that affect the output such as economic factors, sanitation, and customs. Concluded that the stunting interventions in Kawasan Sehat Oebelo were effective and all components of inputs-processes-outputs were running well.